Doing research to improve teaching and learning : a guide for college and university faculty - Williams, Kimberly M (Routledge, 2015)
"Given the increased accountability at the college and university level, one of the most promising ways for faculty at institutions of higher education to improve their teaching is to capitalize upon their skills as researchers. This book is a step-by-step guide for doing research to inform and improve teaching and learning. With background and instruction about how to engage in these methodologies--including qualitative, quantitative, and mixed methods--Doing Research to Improve Teaching and Learning provides examples across disciplines of how to use one's research skills to improve teaching. This valuable resource equips faculty with the skills to collect and use different types of research evidence to improve teaching and learning in any college and university classroom"--